TESTING LANGUAGES FOR SPECIFIC PURPOSES - Petrashchuk, Olena P. (Proceedings of National Aviation University (archive), 2010)
The article is about a problem of the English language for specific (professional) purposes. Language for specific purposes is being analysed in comparison with the General Language. Oral proficiency interview is being described as an effective tool of oral proficiency measurement. Regarding high reliability of the test results, the ways to validate the oral proficiency interview as a part of oral test in English for specific purposes aimed are proposed.